Determination of creep damage properties from miniature thin beam bending using an inverse approach - Lu, J.; Campbell-Brown, A.; Tu, Shan-Tung; Sun, Wei (Trans Tech Publications, 2017)
In this work, a novel method for determining the creep damage properties which can be used to represent the full life until failure from a miniature bending creep test specimen is developed based on a mathematical analysis and an inverse approach. Using the Kachanov-Rabotnov creep damage model, a mathematical expression for the deflection of a simply supported, rectangular miniature thin beam creep test specimen, under three-point bending (TPB), is derived. The outputs of these equations are iterated numerically using a MATLAB program. The time-dependent deflection curves are computed as the virtue TPB tests at various loads. The accuracy of the mathematical solutions is evaluated by the corresponding results obtained from finite element analysis. On this basis, an inverse method is then developed to obtain the creep and damage constants using a MATLAB optimisation scheme, where the primary creep is neglected. The results obtained for a power plant Grade 91 Cr steel is used for demonstration. The inverse approach developed has potential applications for assessing the high temperature material strength as part of a NDT procedure and for deriving the full life creep damage constitutive properties from a small volume of material, in particular, for various microstructure regions within a heat-affected zone of weldments, e.g. of power plant pipelines and aero-engine components.